1952
DOI: 10.1039/jr9520004569
|View full text |Cite
|
Sign up to set email alerts
|

889. A study of the supercooling of drops of some molecular liquids

Abstract: The extent to which various liquid drops may be supercooled has been observed by examining the appearance of clouds of such drops in a beam of light a t different temperatures. For most of the liquids studied the great majority of the drops did not freeze until a comparatively narrow range of temperature had been reached far below the melting point. In this range where the drops freeze spontaneous homogeneous nucleation is assumed to occur. This is discussed in the light of current theories of nucleation pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0

Year Published

1965
1965
2005
2005

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(78 citation statements)
references
References 0 publications
5
73
0
Order By: Relevance
“…9 The material constants for i-PP used in the analysis are listed in Table III. The fold-surface free energy, e , for self-nucleated block propylene-ethylene copolymer and i-PP are listed in Table IV.…”
Section: Figurementioning
confidence: 99%
“…9 The material constants for i-PP used in the analysis are listed in Table III. The fold-surface free energy, e , for self-nucleated block propylene-ethylene copolymer and i-PP are listed in Table IV.…”
Section: Figurementioning
confidence: 99%
“…10 Hence, it is considered that CJ and CJe values of the copolyesters are equal to those of the pure PBN homopolymer, respectively. The lateral surface free energy CJ is related with the heat of fusion 11H as the following Thomas-Stavely relation 20 CJ= a!1H(a0b 0 ) 112 (8) where a is an empirical constant and a 0 is the chain stem width. The heat of fusion of copolymer can be considered as the sum of the heat of fusion of homopolymer and the heat of mixing of the pure melt with a noncrystallizable component.…”
Section: ------------mentioning
confidence: 99%
“…The ratio of G 0 (III)/G 0 (II) for the best fits is about 1.4 ϫ 10 3 . In the past, most assessments of the surface free energies, , have relied on the use of the modified Thomas-Staveley equation, 11 where the value ␣ ϭ 0.1 was assumed to be universal. This expression is…”
Section: ϫ2mentioning
confidence: 99%
“…This microscopic study also showed that there was no morphological change between regimes II and III. Finally, the ␣ value in the modified Thomas-Staveley equation 11 will be discussed.…”
Section: Introductionmentioning
confidence: 99%